Assessment of Chatbot Powered App on Doctor-Patient Communication at Chukwemeka Odumegwu Ojukwu Teaching Hospital, Awka, Anambra State - Chinelo Ebele Uchendu; Vincent Precious Chioma; Omolara Oluwabusayo Akin-Odukoya; Timothy Ekeledirichukwu Onyejelem (Britain International for Academic Research (BIAR) Publisher, 2026)
This study assessed the impact of chatbot-powered applications on doctor–patient communication at Chukwuemeka Odumegwu Ojukwu Teaching Hospital. The research explored the extent of app usage, its effectiveness in enhancing clarity, feedback, and timeliness, the challenges faced by doctors and patients, and the overall effect on communication quality. A sample size of 283 was determined using Taro Yamane’s formula from a total population of 958 (comprising doctors and patients), with 270 valid responses retrieved through online questionnaires. Data were analyzed using descriptive statistics and simple percentages. Findings revealed that most respondents were aware of the chatbot app and acknowledged its contribution to improving communication. The app was reported to enhance clarity, timeliness, and the provision of accurate medical information. Respondents also noted that it made understanding medical instructions easier and fostered trust between doctors and patients. However, challenges such as technical issues, limited handling of complex queries, and concerns about privacy and data security were highlighted. Despite these, the app’s overall impact on doctor–patient communication was largely positive. The study recommends continuous improvement of the chatbot app by integrating advanced features, ensuring stronger privacy safeguards, and enhancing technical support. For doctors, training on effective use of the app is advised, while patients should be sensitized to increase adoption. Policymakers are encouraged to support the integration of artificial intelligence in healthcare to strengthen communication systems in hospitals. The study concludes that chatbot-powered apps can play a vital role in transforming healthcare communication when properly optimized.